Rock fragmentation measurements in sublevel caving: field tests at LKAB’s Malmberget mine - Manzoor, S; Gustafson, A; Schunnesson, H; Tariq, M; Wettainen, T (Caving 2022: Proceedings of the Fifth International Conference on Block and Sublevel Caving, 2022)
Ground vibrations from blasting are one of the main challenges faced by mines located near populated areas. To confront this challenge, Luossavaara-Kiirunavaara Aktiebolag’s Malmberget underground iron ore mine in Sweden tested a change in blast design. Specifically, it tested production holes with smaller diameter to decrease the explosive detonated per delay and thereby lower the ground vibrations. However, smaller holes normally increase hole deviation and may also influence the chargeability of the holes, both of which have a negative effect on fragmentation. Therefore, a detailed evaluation was required before a final decision could be made. To evaluate the fragmentation, field tests were carried out in two drifts of an orebody in the mine. Cameras were mounted in both drifts to record the fragmentation in every loaded bucket. The recording was configured to start by a motion detection parameter; consequently, every movement underneath the cameras was captured. The recording process continued for over a year and resulted in more than 15,000 videos. To analyse such an enormous data for fragmentation, an internally developed quick rating system (QRS) was used to evaluate a total of 7,258 loaded buckets. Blasted rock in the load–haul–dump buckets was classified as fine, medium, coarse, or oversize based on the median fragment size (X50). This paper explains the experimental setup of the test and the analysis procedures. The test results showed that smaller diameter boreholes tend to reduce the median fragment size slightly, and therefore favour the reduction of borehole diameter to deal with the ground vibration problem. The influence of borehole deviation and chargeability was not specifically investigated in this test and need further research to better understand subsequent fragmentation variations.
Keywords: borehole diameter